Does bull temperament impact growth performance and semen quality? - Braz, Karoline Maria Gil; Monteiro, Fabio Morato; Fernandes, Luana Gomes [UNESP]; Rodrigues, Naiara Nantes [UNESP]; Peixoto Jr, Kléber da Cunha; Green, Renata Elisa; Cortez, Adriana; Crespilho, André Maciel (Elsevier, 2020)
The aim of this study was to evaluate the influence of temperament on body weight and reproductive performance of Nelore bulls. Temperament of 24 young bulls was assessed by chute score (CS) and flight speed (FS). Based on the results of two consecutive evaluations (M1 and M2), bulls were divided into two groups according to their CS: Reactive (n = 12) and Calm (n = 12). Blood samples were collected from both groups for testosterone and cortisol analysis once a month for 4 months. Similarly, over 4 months semen was collected along with scrotal and ocular globe thermography for further analysis, and body weight (BW) was recorded. Reactive bulls showed greater CS (P<0.0001) and FS (P<0.01) and lower BW (P<0.01) than Calm bulls. Cortisol concentrations in serum were reduced in the Calm group (P<0.05), but serum testosterone concentrations did not differ between groups with distinct behaviour. The scrotal thermography on Reactive bulls presented greater temperature at the caudal pole of testicle (P<0.05). However, semen quality (volume, kinetics, morphology and concentration) did not differ between the two groups. The results of this study demonstrated that bulls with reactive temperament were affected on their cortisol concentrations leading to loss of body weight and greater testicles temperature. The temperament of Nelore bulls had no impact on testosterone concentrations or fresh semen quality, even with increased serum cortisol and scrotal temperature.
Keywords: Bull; Cortisol; Live weight; Scrotal thermography; Semen; Temperament